A method for preparing high molecular weight polyethylene

By using porous polymer microspheres supported by metallocene doped Zieglernata composite catalyst, combined with a gas-phase fluidized bed and slurry reactor, the problem of preparation of narrow molecular weight distribution high molecular weight polyethylene was successfully solved, achieving efficient polymer preparation and excellent processing performance.

CN116425906BActive Publication Date: 2025-03-11PARK SENJING NEW ENERGY MATERIALS (SHANGHAI) CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310454944.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2025-03-11
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high molecular weight polyethylene with narrow molecular weight distribution in the prior art, and the mixing of Ziegler-Natta catalyst and metallocene catalyst will reduce the effectiveness of the catalyst.

Method used

Porous polymer microspheres supported by metallocene doped Zieglernata composite catalyst was used to perform polymerization reactions to prepare high molecular weight polyethylene by combining a gas-phase fluidized bed reactor and a slurry reactor.

Benefits of technology

The preparation of high-molecular weight polyethylene with narrow molecular weight distribution is achieved, the processing performance of polymers is improved, the application needs of materials for lithium-ion battery separators is met, and energy savings are achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for preparing high molecular weight polyethylene, comprising injecting ethylene into an ethylene refining unit to obtain refined ethylene; injecting a porous polymer microsphere loaded metallocene-doped Ziegler-Natta composite catalyst and a co-catalyst into a catalyst prefabrication unit to mix and obtain a catalyst composition; injecting the refined ethylene and the catalyst composition into a gas phase fluidized bed reactor respectively for polymerization reaction; discharging the polymer material into a slurry reactor, and continuing the polymerization reaction in the presence of a solvent; and treating the discharged powder to obtain the high molecular weight polyethylene powder. The present invention uses porous polymer microspheres as a carrier, doping a trace amount of metallocene in the Ziegler-Natta catalyst, and the obtained composite catalyst is used for the synthesis of high molecular weight polyethylene, and a high molecular weight polyethylene with a narrow molecular weight distribution can be obtained, which can meet the application needs of materials for lithium ion battery separators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyethylene preparation, and in particular to a method for preparing high molecular weight polyethylene with narrow molecular weight distribution. Background Art

[0002] High molecular weight polyethylene is a linear thermoplastic engineering plastic with excellent comprehensive properties. The molecular weight of ordinary polyethylene is generally between 40,000 and 120,000, while that of high molecular weight polyethylene can reach 1 to 4 million. With the substantial increase in molecular weight, some properties of the resin will undergo sudden changes, such as good wear resistance; strong impact resistance, and the impact strength remains high at low temperatures; good self-lubrication, etc. High molecular weight polyethylene can and is replacing carbon steel, stainless steel, bronze, etc., and is widely used in textiles, papermaking, food machinery, transportation, ceramics, coal and other fields.

[0003] High molecular weight polyethylene includes ultra-high molecular weight polyethylene and ultra-high molecular weight polyethylene. Ultra-high molecular weight polyethylene generally refers to linear structural polyethylene with a viscosity average molecular weight in the range of 300,000 to 1.5 million, and ultra-high molecular weight polyethylene is a linear structural polyethylene with a viscosity average molecular weight greater than 1.5 million. Depending on the molecular weight of high molecular weight polyethylene, its application is also different. For example, high molecular weight polyethylene resin with a molecular weight > 4 million is mainly used for the production of fibers; high molecular weight polyethylene resin with a molecular weight of 2 million to 4 million is mainly used for the production of pipes; high molecular weight polyethylene resin with a molecular weight of 500,000 to 1.5 million is mainly used for the production of lithium-ion battery separators.

[0004] Generally speaking, the performance parameters of high molecular weight polyethylene powder, such as relative molecular weight distribution, particle morphology, and particle size distribution, will be affected by factors such as catalysts and polymerization processes, and these performance parameters will affect the processability of polymer powders, and then affect product performance. In the prior art, ordinary Ziegler-Natta catalysts can only prepare high molecular weight polyethylene with a wide molecular weight distribution. Metallocene catalysts can prepare high molecular weight polyethylene with a narrow molecular weight distribution, but the molecular weight of the resulting polyethylene is not high enough. Chinese patent CN1729206A reports that some components of the Ziegler-Natta catalyst system have certain toxicity to the metallocene catalyst system, that is, it is generally believed that mixing the two will reduce the use effect of the catalyst. Chinese patent CN1413222A reports the use of Ziegler-Natta / metallocene mixed catalysts for the preparation of bimodal polyolefins with a wide molecular weight distribution.

[0005] Therefore, how to further develop a new method for preparing high molecular weight polyethylene to obtain high molecular weight polyethylene with a narrow molecular weight distribution remains a hot topic in this field. Summary of the invention

[0006] The present invention aims to provide a method for preparing high molecular weight polyethylene to solve the above-mentioned defects existing in the background technology.

[0007] A method for preparing high molecular weight polyethylene comprises the following steps:

[0008] S1. Inject ethylene into an ethylene refining unit, remove impurities and moisture through a desulfurization and dechlorination tower, a CO removal tower, a deoxygenation tower and a drying tower to obtain refined ethylene;

[0009] S2, injecting the metallocene-doped Ziegler-Natta composite catalyst supported by porous polymer microspheres and the co-catalyst into the catalyst prefabricated unit and mixing them thoroughly to obtain a catalyst composition;

[0010] S3, respectively injecting the refined ethylene and the catalyst composition into a gas phase fluidized bed reactor to carry out polymerization reaction, the polymerization temperature is controlled at 85-105°C, the pressure is 2.5-3.5MPa, the gas flow rate is controlled at 0.5-1.2m / s, and the residence time is 0.5-1.5h;

[0011] S4, the polymer material is discharged into the slurry reactor, and the polymerization reaction is continued in the presence of a solvent, the polymerization temperature is controlled at 75-95°C, the pressure is 0.3-1.5MPa, the material residence time is 40-80min, and the material level is controlled at 35-75%;

[0012] S5. The discharged powder enters a degassing tower and a drying tower to remove unreacted monomers, and then enters a treatment unit to be treated with nitrogen containing a small amount of water vapor to fully remove the activity of the unconsumed co-catalyst, and finally obtain the high molecular weight polyethylene powder.

[0013] The porous polymer microsphere-supported metallocene-doped Ziegler-Natta composite catalyst refers to a composite catalyst with porous polymer microspheres as carriers, Ziegler-Natta catalyst as main catalyst, and a trace amount of metallocene catalyst doped. Preferably, the doping amount of the metallocene is 0.01-2% of the amount of the Ziegler-Natta catalyst, and more preferably, the doping amount is 0.05-0.1% of the amount of the Ziegler-Natta catalyst.

[0014] The porous polymer microsphere-supported metallocene-doped Ziegler-Natta composite catalyst is prepared by the following method:

[0015] Step 1: reacting porous polymer microspheres with alkyl magnesium chloride in a solvent at 45-50° C. for 10-15 hours, wherein the weight ratio of the porous polymer microspheres to the alkyl magnesium nitride is 1:2-25, the porous polymer microspheres are copolymers of styrene and acrylonitrile, and the average pore size of the porous polymer microspheres is 15-35 nm; the size of the porous polymer microspheres is 2-6 μm ;

[0016] Step 2, reacting the product of step 1 with an aluminoxane compound in a solvent at 45-50° C. for 10-12 hours, wherein the weight ratio of the porous polymer microspheres to the aluminoxane compound is 20:1-3;

[0017] Step 3, reacting the product of step 2 with titanium tetrachloride in a solvent at 45-65° C. for 3-6 hours, wherein the weight ratio of the porous polymer microspheres to titanium tetrachloride is 1:3-5;

[0018] Step 4, adding metallocene to the product of step 3, reacting at 45-50° C. for 10-12 hours to obtain the porous polymer microsphere-loaded metallocene-doped Ziegler-Natta composite catalyst, wherein the weight ratio of the metallocene to the porous polymer microsphere is 1:75-100.

[0019] The metallocene described in the present invention refers to an organic metal coordination compound formed by the connection between a transition metal and cyclopentadiene, such as cyclopentadienyl titanium trichloride (CAS: 1270-98-0), bis(cyclopentadienyl) titanium dichloride (CAS: 1271-19-8), bis(cyclopentadienyl) zirconium dichloride (CAS: 1291-32-3), bis(pentamethylcyclopentadienyl) zirconium dichloride (CAS: 54039-38-2), etc., preferably cyclopentadienyl titanium trichloride or bis(cyclopentadienyl) titanium dichloride.

[0020] The alkyl magnesium chloride of the present invention can be a common component in the art, such as methyl magnesium chloride, ethyl magnesium chloride or butyl magnesium chloride.

[0021] The aluminoxane compound of the present invention can be a commonly used component in the art, such as methylaluminoxane or modified methylaluminoxane.

[0022] The applicant unexpectedly discovered that by using porous polymer microspheres as carriers and doping a trace amount of metallocene in a Ziegler-Natta catalyst to prepare a composite catalyst for the synthesis of high molecular weight polyethylene, high molecular weight polyethylene with a narrow molecular weight distribution can be unexpectedly obtained. Based on the above discovery, the present invention was completed.

[0023] The porous polymer microspheres loaded with metallocene-doped Ziegler-Natta composite catalyst may also include an internal electron donor and / or an external electron donor, and the role of the internal electron donor and the external electron donor is well known in the art, and the selection and dosage of the components can be increased or decreased or adjusted according to the actual needs of the polyethylene product. For example, the internal electron donor can be selected from ethers or ester compounds, including but not limited to cyclobutyl-1,1-dimethanol dimethyl ether, 1,3-diethers, 1,3-propylene glycol dimethyl ether, 2,2-diisobutyl-1,3-propylene glycol dimethyl ether, cyclopentyl-1,1-dimethanol dimethyl ether, 1,3-glycol ester compounds, di-n-butyl phthalate, diisobutyl phthalate, ethyl benzoate, dibutyl phthalate, etc.; the external electron donor can be selected from alkoxysiloxane compounds.

[0024] In the preparation step S2 of the high molecular weight polyethylene of the present invention, the amounts of the catalyst and the co-catalyst are respectively: the molar ratio of the co-catalyst to the catalyst is 10-200:1, preferably 30-80:1.

[0025] The co-catalyst includes but is not limited to trimethylaluminum, triethylaluminum, triisobutylaluminum, diisobutylaluminum monochloride and other organic aluminum compounds, preferably triethylaluminum.

[0026] In step S4, the solvent may be selected from at least one of hexane, heptane, pentane and isopentane. Hydrogen may be used to adjust the MFR and relative molecular weight and their distribution according to the characteristics of the final product. The material level is controlled by the polymerization material level, and the material level is preferably controlled at 50-55%.

[0027] The high molecular weight polyethylene prepared by the present invention has excellent processing performance compared with conventional high molecular weight polyethylene, and has a narrow molecular weight distribution, which can meet the application needs of lithium ion battery separator materials. The present invention fully utilizes the pressure difference between the gas phase reactor and the slurry reactor to realize material transportation, saves energy, and can combine reactors in different ways according to production needs to meet the production needs of different products. DETAILED DESCRIPTION

[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only used as examples, but are not used to limit the scope of the present invention. Those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalent solutions, and other technical solutions that do not deviate from the spirit and scope of the present invention.

[0029] The instruments or reagents in the examples of the present invention that do not indicate the manufacturer are all conventional commercial instruments or reagents. The molecular weight distribution is determined by high temperature gel chromatography to determine the weight average molecular weight Mw and number average molecular weight Mn of the polymer, and then the molecular weight distribution index is calculated as Mw / Mn.

[0030] Example 1

[0031] Preparation of porous polymer microspheres supported metallocene-doped Ziegler-Natta composite catalyst:

[0032] 1) 20 g of porous polymer microspheres (styrene and acrylonitrile copolymer, average pore size of microspheres is 22.6 nm; microsphere size is 4.7 um) and 360 g of methyl magnesium chloride are reacted in hexane solvent at 50° C. for 12 h;

[0033] 2) Continue to add 1g of methylaluminoxane and react at 50°C for 12h;

[0034] 3) Continue to add 100g titanium tetrachloride and react at 65°C for 5h;

[0035] 4) Finally, 0.2 g of bis(cyclopentadienyl)titanium dichloride was added and reacted at 50° C. for 10 h to obtain the porous polymer microsphere-supported metallocene-doped Ziegler-Natta composite catalyst.

[0036] Example 2

[0037] Preparation of high molecular weight polyethylene:

[0038] 1) Injecting ethylene into an ethylene refining unit, removing impurities and moisture through a desulfurization and dechlorination tower, a CO removal tower, a deoxygenation tower and a drying tower to obtain refined ethylene;

[0039] 2) injecting the porous polymer microspheres loaded with metallocene-doped Ziegler-Natta composite catalyst and triethylaluminum co-catalyst prepared in Example 1 into a catalyst prefabrication unit and mixing them thoroughly to obtain a catalyst composition, wherein the Al / Ti molar ratio is 75 / 1;

[0040] 3) Injecting the refined ethylene and the catalyst composition into a gas phase fluidized bed reactor respectively to carry out polymerization reaction, the polymerization temperature is controlled at 95°C ± 5°C, the pressure is 3.0MPa ± 0.3MPa, the gas flow rate is controlled at 0.8m / s ± 0.2m / s, and the residence time is 1h;

[0041] 4) The polymer material is discharged into the slurry reactor and the polymerization reaction is continued in the presence of a solvent. The polymerization temperature is controlled at 90°C ± 5°C, the pressure is 0.6MPa ± 0.1MPa, the material residence time is 70min, and the material level is controlled at 55% ± 5%;

[0042] 5) The discharged powder enters a degassing tower and a drying tower to remove unreacted monomers, and then enters a treatment unit to be treated with nitrogen containing a small amount of water vapor to fully remove the activity of the unconsumed co-catalyst, and finally obtains the high molecular weight polyethylene powder. The weight average molecular weight of the product is 2.35 million, and the molecular weight distribution index is 2.06.

[0043] Comparative Example

[0044] Preparation of high molecular weight polyethylene using conventional Ziegler-Natta catalysts:

[0045] 1) Injecting ethylene into an ethylene refining unit, removing impurities and moisture through a desulfurization and dechlorination tower, a CO removal tower, a deoxygenation tower and a drying tower to obtain refined ethylene;

[0046] 2) injecting the Ziegler-Natta catalyst and the triethylaluminum co-catalyst into the catalyst prefabrication unit and mixing them thoroughly to obtain a catalyst composition with an Al / Ti molar ratio of 75 / 1;

[0047] 3) Injecting the refined ethylene and the catalyst composition into a gas phase fluidized bed reactor respectively to carry out polymerization reaction, the polymerization temperature is controlled at 95°C ± 5°C, the pressure is 3.0MPa ± 0.3MPa, the gas flow rate is controlled at 0.8m / s ± 0.2m / s, and the residence time is 1h;

[0048] 4) The polymer material is discharged into the slurry reactor and the polymerization reaction is continued in the presence of a solvent. The polymerization temperature is controlled at 90°C ± 5°C, the pressure is 0.6MPa ± 0.1MPa, the material residence time is 70min, and the material level is controlled at 55% ± 5%;

[0049] 5) The discharged powder enters the degassing tower and drying tower to remove the unreacted monomers, and then enters the treatment unit, where it is treated with nitrogen containing a small amount of water vapor to fully remove the activity of the unconsumed co-catalyst, and finally obtains high molecular weight polyethylene powder. The weight average molecular weight of the product is 2.29 million, and the molecular weight distribution index is 3.32.

[0050] The molecular weight distribution index of the high molecular weight polyethylene prepared by the present invention is 40% lower than that of the high molecular weight polyethylene prepared by using a conventional Ziegler-Natta catalyst, and the high molecular weight polyethylene prepared by the present invention has the advantage of a narrow molecular weight distribution, and can meet the application requirements of materials for lithium ion battery diaphragms.

[0051] It should be understood by those skilled in the art that the above embodiments are only examples and do not limit the present invention. The purpose of the present invention has been fully and effectively achieved. The functions and principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be modified or altered in any way without departing from the principles.

Claims

1. A method for preparing high molecular weight polyethylene, characterized in that: The steps include: S1. Inject ethylene into an ethylene refining unit, remove impurities and moisture through a desulfurization and dechlorination tower, a CO removal tower, a deoxygenation tower and a drying tower to obtain refined ethylene; S2, injecting the porous polymer microsphere-supported metallocene-doped Ziegler-Natta composite catalyst and the co-catalyst into the catalyst prefabricated unit and mixing them thoroughly to obtain a catalyst composition; S3, respectively injecting the refined ethylene and the catalyst composition into a gas phase fluidized bed reactor to carry out polymerization reaction, the polymerization temperature is controlled at 85-105°C, the pressure is 2.5-3.5MPa, the gas flow rate is controlled at 0.5-1.2m / s, and the residence time is 0.5-1.5h; S4, the polymer material is discharged into the slurry reactor, and the polymerization reaction is continued in the presence of a solvent, the polymerization temperature is controlled at 75-95°C, the pressure is 0.3-1.5MPa, the material residence time is 40-80min, and the material level is controlled at 35-75%; S5, the discharged powder enters a degassing tower and a drying tower to remove unreacted monomers, and then enters a treatment unit to be treated with nitrogen containing a small amount of water vapor to fully remove the activity of the unconsumed co-catalyst, and finally obtain the high molecular weight polyethylene powder; The porous polymer microsphere-supported metallocene-doped Ziegler-Natta composite catalyst refers to a composite catalyst using porous polymer microspheres as a carrier, a Ziegler-Natta catalyst as a main catalyst, and doped with a trace amount of metallocene catalyst, and is specifically prepared by the following method: Step 1, reacting porous polymer microspheres with alkyl magnesium chloride in a solvent at 45-50° C. for 10-15 hours, wherein the weight ratio of the porous polymer microspheres to the alkyl magnesium chloride is 1:2-25, the porous polymer microspheres are copolymers of styrene and acrylonitrile, and the average pore size of the porous polymer microspheres is 15-35 nm; the size of the porous polymer microspheres is 2-6 um; Step 2, reacting the product of step 1 with an aluminoxane compound in a solvent at 45-50° C. for 10-12 hours, wherein the weight ratio of the porous polymer microspheres to the aluminoxane compound is 20:1-3; Step 3, reacting the product of step 2 with titanium tetrachloride in a solvent at 45-65° C. for 3-6 hours, wherein the weight ratio of the porous polymer microspheres to titanium tetrachloride is 1:3-5; Step 4, adding metallocene to the product of step 3, reacting at 45-50° C. for 10-12 hours to obtain the porous polymer microsphere-loaded metallocene-doped Ziegler-Natta composite catalyst, wherein the weight ratio of the metallocene to the porous polymer microsphere is 1:75-100.

2. The method according to claim 1, characterized in that The doping amount of the metallocene is 0.01-2% of the amount of the Ziegler-Natta catalyst.

3. The method according to claim 1, characterized in that The metallocene is cyclopentadienyl titanium trichloride or bis(cyclopentadienyl) titanium dichloride.

4. The method according to claim 1, characterized in that The alkyl magnesium chloride is selected from at least one of methyl magnesium chloride, ethyl magnesium chloride or butyl magnesium chloride.

5. The method according to claim 1, characterized in that The aluminoxane compound is methylaluminoxane or modified methylaluminoxane.

6. The method according to claim 1, characterized in that In step S2, the molar ratio of the co-catalyst to the catalyst is 30-80:

1.

7. The method according to claim 1, characterized in that The co-catalyst is triethylaluminum.

8. A high molecular weight polyethylene prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Mixed ziegler / metallocene catalysts for production of bimodal polyolefins

    CN1413222A

  • Processes for transitioning between metallocene and ziegler-natta polymerization catalysts

    CN1729206A

  • Composite catalyst for producing polyethylene with wide molecular weight distribution as well as production method and application thereof

    CN102887967A

  • Ultrahigh-molecular-weight polyethylene catalyst as well as preparation method and application thereof

    CN113174002A